Responses of the wintertime auroral E-region neutral wind to varying levels of geomagnetic activity - Zhan, Weijia; Keappler, Stephen R. (Frontiers in Astronomy and Space Sciences, 2023)
Introduction: The auroral E-region is an important interface where forces from the magnetosphere and the lower atmosphere converge and have a significant effect on the vertical structure of the neutral winds. The resulting vertical neutral wind structure has been reported to be associated with altitude-dependent and nonlinear effects from different forces. We conduct a statistical examination of the reactions of wintertime neutral winds to four various degrees of geomagnetic activity, with a focus on the impacts of ion drag. Methods: We derive neutral winds using the PFISR measurements covering 2010–2019 and will give a statistical view of the auroral E-region neutral wind with a focus on the winter nighttime during different disturbed conditions. We investigate the effects of the geomagnetic activity on the neutral winds and the tidal components by dividing the dataset into 4 subsets. Tidal decomposition is conducted by least square fitting of the seasonal median winds to obtain the mean, diurnal amplitude, diurnal phase, semidiurnal amplitude, and semidiurnal phase. Results and discussion: We find that 1) when geomagnetic activity increases, dawn-dusk asymmetry exists in both zonal and meridional winds in the upper E-region with stronger zonal wind in the dusk sector than in the dawn sector and much stronger meridional wind in the dawn sector than in the dusk sector. 2) Tidal decomposition results reveal that geomagnetic activity has more significant effects on the meridional diurnal amplitude than zonal diurnal amplitude while the zonal and meridional semidiurnal amplitudes show similar changes when the geomagnetic activity increases. In addition, the maximum semidiurnal amplitude, particularly in the zonal direction, appears at a higher altitude with larger values as geomagnetic activity increases, indicating an ascending transition altitude for the semidiurnal oscillations. The ascending trend of maximum semidiurnal amplitude appearing at higher altitudes during more disturbed conditions has not been reported before. 3) Zonal wind over 110 km demonstrates increasing ion drag effects in the evening sector and the effects of coupled ion drag and other factors after midnight.